Legal Review Of The Role Of Witness And Victim Protection Institutions Under Indonesian Law - Agus Sugiarto (Fox Justi : Jurnal Ilmu Hukum, 2024)
This research examines the role of witness and victim protection institutions in the legal context in Indonesia. The role of this institution is becoming increasingly important in handling criminal cases involving witnesses and victims, who are often vulnerable to threats, pressure and intimidation. This research uses a normative legal analysis method by referring to statutory regulations, court decisions, and related legal literature. The results of this research show that the Witness and Victim Protection Agency (LPSK) has a vital role in providing protection, assistance and support to witnesses and victims of criminal acts in Indonesia. Through the various roles it carries out, such as providing legal assistance, providing physical and psychological protection, and promoting cooperation with related institutions, LPSK plays a role in ensuring that witnesses and victims can face the justice process more safely and with dignity. However, there are several challenges that need to be overcome, including budget constraints and the need for increased inter-agency collaboration. Therefore, joint efforts from LPSK, the government, related institutions and the community are needed to increase protection and security for witnesses and victims, so that they can obtain equal and dignified justice in the criminal justice system.